Performance Improvement And Production Capacity Of Brownte (Eggplant Brownies) Healty Food Through Technology Transfer To The Concept Of "Open Kitchen" And "Franchise" As a Special Food Product Of Batu City - Dr.Teti Estiasih (Journal of Innovation and Applied Technology, 2015)
ABSTRACT Eggplant Brownies (Brownte) is one of the culinary diversification in the Batu  City. "Sentra (Selera Nusantara)" has developed a unique food-based form of brownies healthy vegetables since 2010 with brownies carrots, tomatoes, corn, mustard greens. with the name Brownty (Healthy Brownies). The advantage of Brownty is of bioactive compounds from vegetables so it proved Brownty as one of the functional food for health. Outlets "Griya Brownte" which has a program 'Brownty Cooking Show' in the concept of "Open Kitchen" that consumers can enjoy a live presentation as well as how to cook Brownty. The concept of "Open Kitchen" aims to demonstrate the quality of materials and food processing that can be seen directly by consumers. PT Sentra also provides an opportunity for partnership cooperation Brownty healthy snacks in the form of Franchise by investing 25 million a facility such as the right partner and use the brand Brownty for 5 years, partnerships and employee training and supplies equipment for the production and marketing Brownty. The presence of IPTEKDA LIPI XIV activity has provided facilities for technology transfer in the form of food mixer, gas baking oven, steamers, production tables, showcase with freezer to increase production capacity Brownty perfomance and become competitive health food as souvenirs typical of Batu City. Keywords: brownies, open kitchen, franchise